2004
DOI: 10.1165/rcmb.2003-0314oc
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function of the Vascular Endothelial Growth Factor Receptor FLT-1 in Human Eosinophils

Abstract: Vascular endothelial growth factor (VEGF) is highly expressed in the airway of patients with asthma. Whether VEGF affects eosinophil function in vitro and if VEGF receptors are involved was tested. Eosinophils were from venous blood of healthy donors. Cell migration was studied by micropore filter assays. Signaling mechanisms required for VEGF-dependent migration were tested using signaling enzyme blockers. Expression of flt-1 and KDR/flk-1 mRNA in eosinophils was demonstrated in reverse transcriptase-polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 26 publications
3
41
0
2
Order By: Relevance
“…It appears that basophils, by expressing VEGF-2/KDR and not VEGFR-1/Flt-1, differ from the vast majority of monocytes (38,39,41,62), eosinophils (42), and neutrophils (43) that express VEGFR-1/Flt-1, and not VEGFR-2/KDR. VEGFR-1/Flt-1 appears to mediate chemotaxis in human monocytes (38,39), neutrophils (43), and eosinophils (42).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It appears that basophils, by expressing VEGF-2/KDR and not VEGFR-1/Flt-1, differ from the vast majority of monocytes (38,39,41,62), eosinophils (42), and neutrophils (43) that express VEGFR-1/Flt-1, and not VEGFR-2/KDR. VEGFR-1/Flt-1 appears to mediate chemotaxis in human monocytes (38,39), neutrophils (43), and eosinophils (42).…”
Section: Discussionmentioning
confidence: 98%
“…VEGFR-1/Flt-1 appears to mediate chemotaxis in human monocytes (38,39), neutrophils (43), and eosinophils (42). Endothelial cells express both VEGFR-1/Flt-1 and VEGFR-2/KDR (63), and whereas VEGFR-2/KDR activates cellular signaling, VEGFR-1/Flt-1 acts as a trap to sequester VEGF from VEGFR-2/KDR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Control animals were injected with control antibody rat IgG. The dose and treatment protocol for anti-Flt-1 Ab in this study have been previously reported to be effective in inhibition of Flt-1-mediated cellular responses (Feistritzer et al, 2004;Ambati et al, 2006).…”
Section: Preparation and Administration Of Compoundsmentioning
confidence: 99%
“…In addition, the results from several studies have indicated that Flt-1-mediated signaling could contribute to pathological conditions in disease (Sköld et al, 2005). Elevated VEGF expression has been documented in asthma (Hoshino et al, 2001) and eosinophil inflammatory responses are dependent on activation of Flt-1 (Feistritzer et al, 2004). In a model of rheumatoid arthritis (RA), blockade of Flt-1 was effective in reducing symptoms of disease, whereas inhibition of the Flk-1 subtype of VEGF receptor was without effect (De Bandt et al, 2003).…”
Section: Introductionmentioning
confidence: 99%